From Neural Crest Development to Cancer and Vice Versa: How p75NTR and (Pro)neurotrophins Could Act on Cell Migration and Invasion? - Wislet, Sabine; Vandervelden, Geoffrey; Rogister, Bernard (Frontiers in Molecular Neuroscience, 2018)
The p75 neurotrophin receptor (p75NTR), also known as low-affinity nerve growth factor, belongs to the tumor necrosis factor family of receptors. p75NTR is widely expressed in the nervous system during the development, as well as, in the neural crest population, since p75NTR has been described as ubiquitously expressed and considered as a neural crest marker. Neural crest cells (NCCs) constitute an transient population accurately migrating and invading, with precision, defined sites of the embryo. During migration, NCCs are guided along distinct migratory pathways by specialized molecules present in the extracellular matrix or on the surfaces of those cells. Two main processes direct NCC migration during the development: (1) an epithelial-to-mesenchymal transition and (2) a process known as contact inhibition of locomotion. In adults, p75NTR remains expressed by NCCs and has been identified in an increasing number of cancer cells. Nonetheless, the regulation of the expression of p75NTR and the underlying mechanisms in stem cell biology or cancer cells have not yet been sufficiently addressed. The main objective of this review is therefore to analyze elements of our actual knowledge regarding p75NTR roles during the development (mainly focusing on neural crest development) and see how we can transpose that information from development to cancer (and vice versa) to better understand the link between p75NTR and cell migration and invasion. In this review, we successively analyzed the molecular mechanisms of p75NTR when it interacts with several coreceptors and/or effectors. We then analyzed which signaling pathways are the most activated or linked to NCC migration during the development. Regarding cancer, we analyzed the described molecular pathways underlying cancer cell migration when p75NTR was correlated to cancer cell migration and invasion. From those diverse sources of information, we finally summarized potential molecular mechanisms underlying p75NTR activation in cell migration and invasion that could lead to new research areas to develop new therapeutic protocols.